A Hindu-Arabic to Hausa number transcription system / Safiriyu Ijiyemi Eludiora and Muhammad Auwal Abubakar - Eludiora, Safiriyu Ijiyemi; Abubakar, Muhammad Auwal (Universiti Teknologi MARA, 2021)
The invention of the numeration system is regarded as one of man's great accomplishments. It greatly helps man express his communication needs and serves as an important tool in language pedagogy, historical linguistics, comparative study of African languages, and computational linguistics. However, the numeral system is reported to be an endangered area being identified in the use and study of language, and in no distant time, the traditional number system of the African indigenous counting systems may lose its contact with the new generation. This paper presents a Hindu-Arabic to Hausa number transcription system. Secondary data used was sourced from literature. Context-Free Grammar (CFG) and Unified Modelling Language (UML) was used to design the system. The system designed was implemented using the Python programming language. Mean Opinion Score (MOS) evaluation approach was used to evaluate the implemented system. The result of the evaluation on Numbers with Single Representations (NSR), and Numbers with Multiple Representations (NMR) is based on three (3) metrics: syllable accuracy, orthography accuracy and syntax accuracy. The experimental respondents', system developed, and human expert average scores on NSR were respectively 0%, 100% and 100% for syllable accuracy, 40.1%, 100% and 100% for orthography accuracy, and 62.8%, 100% and 100% for syntax accuracy. Similarly, the experimental respondents', system developed, and human expert average scores on NMR were respectively 0%, 100% and 100% for syllable accuracy, 21.4%, 100% and 100% for orthography accuracy, and 31.7%, 100% and 100% for syntax accuracy. The system is capable of transcribing cardinal numbers, 1 to 1-billion, and the expert response confirmed its accuracy. The study concluded that among others, the developed system is of great importance in the teaching and learning of the traditional Hausa counting system. Future work on contextual Hausa numeral system analysis is recommended.